"It Is a Village": Translanguaging Pedagogies and Collective Responsibility in a Rural School District. Issue 4 (7th January 2020) - Back, Michele
Abstract : Although rural U.S. school districts are experiencing increases in emergent multilingual learners (EMLLs), many lack the resources for employing TESOL‐specialized staff or training mainstream teachers in how to meet these students' needs (Freeman Field, n.d.). Indeed, professional development (PD) in TESOL is a continued, persistent necessity for all teachers working with linguistically and culturally diverse students (Pettit, 2011). This article examines the role of sustained PD in shaping the beliefs and practices regarding EMLLs of educators in a rural school district. Three focal participants engaged in PD sessions on translanguaging pedagogies. Data from interviews, instructional observations, and focus groups showed articulation of a translanguaging stance. Participants demonstrated pedagogical flexibility and a collective sense of responsibility (indexed by the phrase "it is a village") as well as other beliefs and practices characteristic of translanguaging stance, design, and shifts (García, Ibarra Johnson, & Seltzer, 2017). This study addresses a gap in TESOL research regarding how PD can shape educators' attitudes toward and practices with EMLLs. Furthermore, by incorporating often‐overlooked members of elementary school ecologies, such as literacy coaches and world languages teachers, this study emphasizes the valuable role that these individuals can play in supporting EMLLs schoolwide.